The Effect of Green Innovation, Enviromental, Social and Governance Disclosure, Financial Performance on Value of Corporate with Carbon Tax as A Moderating Variable in Energy Companies Listed on the Indonesia Stock Exchange - Eka Safitri; Tri Ratnawati; Ida Ayu Sri Brahmayanti (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
In the industrial world, especially energy companies are very vulnerable to increasing carbon emissions. Based on the graph managed by the Ministry of Environment and Forestry, it shows that the greenhouse gas emissions that contribute most are the forestry and energy sectors. So that in 2021 Indonesia has officially adopted a carbon tax policy by issuing Law no. 7 of 2021. The purpose of this study is to test and analyze the significant effect of Green innovation, Environmental, Social and Governance Disclosure and financial performance on the Value of corporations with carbon tax as a moderating variable and applying carbon performance as an intervening variable. The method in this study is to take samples by purposive sampling in the form of secondary data, namely financial statements and sustainability reports in 2021 to 2024 on the Indonesian stock exchange, with a sample of 27 companies. To determine the significance of results between variables, researchers use SEM-PLS 3 software. The results of this study are that financial performance has a positive and significant relationship to carbon performance with a t-statistic value of 3.497> 1.96, namely that increasing financial performance can affect carbon performance in reducing greenhouse gas emissions. for the next variable, carbon performance has a positive and significant relationship to company value by showing a t-statistic value of 2.596> 1.96 with the assumption that increasing carbon performance in reducing greenhouse gas emissions will increase the company's value and be trusted by investors and the public. And the last is that financial performance has a negative and significant relationship to company value with carbon performance as an intervening variable, this shows a t-statistic value of 1.994> 1.96, with increasing financial performance can affect carbon performance so that greenhouse gas emissions can be reduced and the company's value increases.